International expansion plan of Softfinança to Canada - Batista, Catarina Silva (2022)
The internationalization process and international market selection for SMEs is a topic with growing importance that depends on a firms’ context and conditions. SMEs seem to rely more in Non-Systematic IMS methods, from which they can select a range of different entry modes. This research focuses on SoftFinança, a Portuguese SME, and the evaluation of its entry in the Canadian market. Primary and secondary data was collected, both quantitative and qualitative, analyzed based on existing relevant literature and IB frameworks. Although promising, the Canadian market imposes challenges greater than benefits for SF, and, combined with other country’s analysis, doesn’t represent the optimal choice.